A Network Pharmacology Analysis of Cang Fu Dao Tan Formula for the Treatment of Obese Polycystic Ovary Syndrome - C.A.I. Meng-Cheng; J.I.N. Yong-Sheng; Y.U. Chao-Qin; Cheng Wen (KeAi Communications Co., Ltd., 2020)
Objective: To explore the potential molecular targets of Cang Fu Dao Tan Formula (CFDTF) in the treatment of obese polycystic ovary syndrome (PCOS) using network pharmacology and bioinformatic approaches. Methods: The potential blood-entry active compounds and targets of CFDTF were retrieved from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), and obese PCOS related gene targets were retrieved from GeneCard databases. A protein-protein interaction (PPI) network of CFDTF component-targets and obese PCOS disease- targets was constructed using STRING. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of the intersection network were conducted using a Bioconductor database. Results: In total, 114 active compounds were screened according to oral bioavailability (OB) and drug similarity (DL), and 328 targets related to these constituents were obtained. Further, 2 559 target genes directly related to obese PCOS were obtained from the GeneCard databases, and 82 genes were obtained from the intersection of the component-target and disease-target PPI network. These genes were mainly involved in response to steroid hormones, nutrient levels and lipopolysaccharide as well as in other biological processes. Their molecular functions were mainly related to nuclear receptor activity, phosphatase binding and cytokine activity, and they were enriched in the cytoplasm, cell membrane and membrane region. Conclusions: CFDTF consists of 114 active compounds that are responsible for its pharmacodynamic effects. It mainly regulates the AGE-RAGE signaling pathway in diabetic complications, bladder cancer, and hepatitis B and in other signaling networks. These findings provide certain theoretical and scientific basis for the treatment of obese PCOS with Chinese medicine.